114k views
5 votes
I don't understand this factorisation
a2+ 4a+3​

User Gowachin
by
5.3k points

1 Answer

1 vote

Answer:


\boxed{\sf (a + 3)(a + 1)}

Explanation:


\sf Factor \: the \: following: \\ \sf \implies {a}^(2) + 4a + 3 \\ \\ \sf The \: factors \: of \: 3 \: that \: sum \: to \: 4 \\ \sf are \: 3 \: and \: 1. \\ \\ \sf So, \\ \sf \implies {a}^(2) + (3 + 1)a + 3 \\ \\ \sf \implies {a}^(2) + 3a + a + 3 \\ \\ \sf \implies a(a + 3) + 1(a + 3) \\ \\ \sf \implies (a + 3)(a + 1)

User Steven Jiang
by
5.1k points